Lewis and Clark - Noonan, Jon (New York : Crestwood House, 1993)
Examines the achivements of the two men who will led the great exploring expedition through territory gained by the Louisiana Purchase.
Includes index.
Keywords: Lewis and Clark Expidition (1804-1806) - Juvenile literature; Lewis, Merriwether , 1774-1908-Juvenile literature; Clark, William, 1770-1838 - Juvenile literature